Thermodynamic Parameters of Complexes of Bivalent Transition Metal Ions 3-(4-Chlorophenyl)-1-2’-Hydroxynaphthyl)-2-Propen-1-One - Mallikarjun, K.G.; Seshadri Naidu, R. (Asian Journal of Chemistry, 2010)
The stability constants of UO22+, Cu2+, Zn2+, CO2+, Ni2+ and Mn2+ complexes of 3-(4´-chlorophenyl)-1(2´-hydroxynaphthyl)-2-propen-1-one (CPHNO) have been determined in 75% (v/v) dioxane-water, acetonewater and 2-ethoxy ethanol-water mixtures using the Bjerrum-Calvin pH titration technique as developed by Irving and Rossottii. The stability constants are in fair agreement with Irving-Williams order. The results obtained are compared with the data available in the literature. Abnormal behaviour of the chelates was observed in acetone-water medium. The thermodynamic parameters such as free energy, ethalpy and entropy changes involved in complexation have been calculated.